IMMU-23. Novel gene-edited CAR-T cell therapy against Diffuse Intrinsic Pontine Glioma. (3rd June 2022) - Balakrishnan, Ilango; Leach, Lillie; Lakshmanachetty, Senthilnath; Pierce, Angela; Madhavan, Krishna; Chatwin, Hannah; Fosmire, Susan; Meadows, Christina; Green, Adam; Fry, Terry; Vibhakar, Rajeev; Kohler, Eric M; et al.
Abstract: BACKGROUND : We identified high expression of CD99 in DIPG tumors and developed a CAR using our newly identified single chain variable fragment (scFv) targeting CD99 incorporating a 4-1BB co-stimulatory domain. This CD99 CAR demonstrated the ability to dramatically shrink the established orthotopic DIPG tumor, however tumor recurrence remains an obstacle to cure, due to a loss of the CAR-T cells as they also express the target antigen, CD99 (fratricide). To overcome this obstacle, we modified these CAR-T by editing out CD99. METHODS : CD99 was knocked-out from the human T cells using CRISPR-cas9 gene-editing and subsequently transduced with our CD99 CAR-encoding virus, and isolated the pure population of CD99KO T-cells. These novel, gene-edited T-cells expressing CD99 CAR ("CD99KO CARs") and the un-edited ones ("CD99 CAR") were tested for tumor-lysis function when co-cultured with DIPG cells. DIPG tumor-bearing mice infused with a one-time dose of CD99KO CAR-T cells or CD99 CAR- or CD19 control CAR-T cells and were monitored for changes in the tumor burden. At the endpoint spleen and bone marrow were isolated to test for CAR+ cell persistence. RESULTS : The CD99KO CAR-T cells demonstrated effective tumor-lysis when co-cultured with DIPG cells. CD99KO CAR-T cells targeting CD99 showed complete clearance of DIPG tumor in orthotopic DIPG mouse models, and no tumor recurrence was seen well-beyond the time frame of expected tumor recurrence after treatment with un-edited CD99 CAR-T cells. There was an un-precedented increase in the xenograft survival, > 200 days, in mice treated with CD99KO CARs and at which time point sustained persistence of CAR+ cells were evident in the animal spleen and bone marrow. CONCLUSIONS : We have generated a new and promising CAR-T cell therapy that is effective against DIPG with enhanced persistence in animal models which is critical for clinical translation.